Determination of Flavonoid and Polyphenol Compounds in Viscum Album and Allium Sativum Extracts - Trifunschi, Svetlana; Munteanu, Melania Florina; Agotici, Vlad; Pintea, Simona; Gligor, Ramona (International Current Pharmaceutical Journal, 2015)
Ethnopharmacology is a new interdisciplinary science that appeared in Europe of the 90, in France, as a necessity claimed by the return to the traditional remedies of each nation. The aim of this study is to identify and quantify the active ingredients of the species Viscum album and Allium sativum, in order to provide a complex chemical characterisation, which is necessary for the use of these plants extracts as natural ingredients in the pharmaceutical industry. The following methods were used: (1) the plant material was harvested from the west-side of Romania (Europe) in July 2014; (2) it was dried quickly and the main active principles were extracted using ethylic alcohol solution (50%); (3) the quantitative analyses of the flavonoids and polyphenols were performed according to a procedure described in the Romanian Pharmacopoeia. FT-IR results showed that the Viscum album extract had the highest content of polyphenolic compounds, for both flavonoids and polyphenols. This is the reason why it can be concluded that alcoholic extracts of mistletoe must be used as supplements for diabetics who require diets with flavonoids or for patients with cancers, degenerative diseases, and particularly cardiovascular diseases, who need an increased amount of polyphenols. DOI: http://dx.doi.org/10.3329/icpj.v4i5.22861 International Current Pharmaceutical Journal, April 2015, 4(5): 382-385